2002
DOI: 10.1038/sj.jea.7500237
|View full text |Cite
|
Sign up to set email alerts
|

Risks to the public from historical releases of radionuclides and chemicals at the Rocky Flats Environmental Technology Site

Abstract: This paper summarizes the methods and results of estimating risks of cancer incidence resulting from plutonium, carbon tetrachloride, and beryllium releases from operations at the Rocky Flats Environmental Technology Site, near Denver, Colorado, from 1953 through 1989. The key findings show that people who lived near the facility were exposed to plutonium mainly through inhalation during routine operations, from a major fire in 1957, and from plutonium resuspended from contaminated soil from an outdoor drum st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Dust samples collected at residences in the surrounding states contained excess plutonium not related to global background fallout, apparently resuspended by the wind from the test site (Cizdziel et al., 1998). Increased incidence of cancers has also been detected in residents downwind of plutonium production facilities at Rocky Flats, Colorado (Johnson, 1981) and Hanford, Washington (Grossman et al., 2003), likely at least partially related to aeolian resuspension of radionuclides: however, other chemicals associated with plutonium production may pose a greater health risk at Rocky Flats (Till et al., 2002).…”
Section: Effects On Environmental Healthmentioning
confidence: 99%
“…Dust samples collected at residences in the surrounding states contained excess plutonium not related to global background fallout, apparently resuspended by the wind from the test site (Cizdziel et al., 1998). Increased incidence of cancers has also been detected in residents downwind of plutonium production facilities at Rocky Flats, Colorado (Johnson, 1981) and Hanford, Washington (Grossman et al., 2003), likely at least partially related to aeolian resuspension of radionuclides: however, other chemicals associated with plutonium production may pose a greater health risk at Rocky Flats (Till et al., 2002).…”
Section: Effects On Environmental Healthmentioning
confidence: 99%
“…Dust samples collected at residences in the surrounding states contained excess plutonium not related to global background fallout, apparently resuspended by the wind from the test site (Cizdziel et al, 1998). Increased incidence of cancers has also been detected in residents downwind of plutonium production facilities at Rocky Flats, Colorado (Johnson, 1981) and Hanford, Washington (Grossman et al, 2003), likely at least partially related to aeolian resuspension of radionuclides: however, other chemicals associated with plutonium production may pose a greater health risk at Rocky Flats (Till et al, 2002).…”
Section: Radioactive Contamination (Radionuclides) In Dustmentioning
confidence: 99%
“…Research on the human health impacts of Rocky Flats on both nuclear weapons workers and the public have been mired in controversy. 14 A major comprehensive study found that airborne exposure to plutonium and carbon tetrachloride was the major contributor to the risk of cancer for both nuclear workers and the public, and these releases came from both routine operations and discrete events such as fires (Till et al 2002). By 1989, there was evidence that corporate contractor Rockwell Industries had been illegally incinerating and storing hazardous and radioactive wastes, and the Federal Bureau of Investigation and the Environmental Protection Agency raided the Rocky Flats plant and prosecuted Rockwell for criminal violations of the Resource Conservation and Recovery Act and the Federal Water Pollution Control Act, resulting in the end of Rockwell's management of the facility (U.S. Department of Energy 2003).…”
Section: Rocky Flats Nuclear Arsenal: Sealed-pit Weaponsmentioning
confidence: 99%